# Class 11 RD Sharma Solutions – Chapter 12 Mathematical Induction – Exercise 12.2 | Set 1

### Prove the following by the principle of mathematical induction:

### Question 1. 1 + 2 + 3 + … + n = n (n +1)/2 i.e., the sum of the first n natural numbers is n (n + 1)/2.

**Solution:**

Let, P (n) = 1 + 2 + 3 + ….. + n = n (n +1)/2.

Attention reader! All those who say programming isn't for kids, just haven't met the right mentors yet. Join the

Demo Class for First Step to Coding Course,specificallydesigned for students of class 8 to 12.The students will get to learn more about the world of programming in these

free classeswhich will definitely help them in making a wise career choice in the future.Step 1:

Now, let us check P(n) for n = 1.

So, P (1) = 1 (1 + 1)/2 = 1.

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

Then, 1 + 2 + 3 + …. + k = k (k + 1)/2 … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

(1 + 2 + 3 + … + k) + (k + 1) = k (k + 1)/2 + (k + 1)

= (k + 1) (k/2 + 1)

= [(k + 1) (k + 2)] / 2

= [(k + 1) [(k + 1) + 1]] / 2

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI) P (n) is true for all n ∈ N.

### Question 2. 1^{2} + 2^{2} + 3^{2} + … + n^{2} = [n (n + 1) (2n + 1)]/6

**Solution:**

Let, P (n) = 1

^{2}+ 2^{2}+ 3^{2}+ … + n^{2}= [n (n + 1) (2n + 1)]/6Step 1:

Now, let us check P(n) for n = 1.

So, P (1) = [1 (1 + 1) (2 + 1)]/6

or, 1 = 1.

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

Then, 1

^{2}+ 2^{2}+ 3^{2}+ … + k^{2}= [k (k + 1) (2k + 1)]/6Step 3:

Now, we have to prove for P(k + 1) is true.

P (k) = 1

^{2}+ 2^{2}+ 3^{2}+ …….. + k^{2}+ (k + 1)^{2}= [k + 1 (k + 2) (2k + 3)] /6= 1

^{2}+ 2^{2}+ 3^{2}+ ……. + k^{2}+ (k + 1)^{2}= [k + 1 (k + 2) (2k + 3)] /6 + (k + 1)

^{2}= (k +1) [(2k

^{2}+ k)/6 + (k + 1)/1]= (k +1) [2k

^{2}+ k + 6k + 6]/6= (k +1) [2k

^{2}+ 7k + 6]/6= (k +1) [2k

^{2}+ 4k + 3k + 6]/6= (k +1) [2k(k + 2) + 3(k + 2)]/6

= [(k +1) (2k + 3) (k + 2)] / 6

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 3. 1 + 3 + 3^{2} + … + 3n – 1 = (3n – 1)/2

**Solution:**

Let P (n) = 1 + 3 + 3

^{2}+ ……. + 3n – 1 = (3n – 1)/2Step 1:

Now, let us check P(n) for n=1.

P (1) = 1 = (3(1) – 1)/2 = (3 – 1)/2 = 2/2 =1

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1 + 3 + 3

^{2}+ ……. + 3k – 1 = (3k – 1)/2 … (i)Step 3:

Now, we have to prove for P(k + 1) is true.

Then,

{1 + 3 + 3

^{2}+ ……. + 3k – 1} + 3k + 1 – 1Using equation (i), we get

= (3k – 1)/2 + 3k

= (3k – 1 + 2 × 3k)/2

= (3 × 3 k – 1)/2

= (3

^{k + 1 }– 1)/2So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 4. 1/1.2 + 1/2.3 + 1/3.4 + … + 1/n(n + 1) = n/(n + 1)

**Solution:**

Let P (n) = 1/1.2 + 1/2.3 + 1/3.4 + … + 1/n(n + 1) = n/(n + 1)

Step 1:

Now, let us check P(n) for n=1.

P (1) = 1/1.2 = 1/(1 + 1)

1/2 = 1/2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1 /1.2 + 1/2.3 + 1/3.4 + … + 1/k(k + 1) + k/(k + 1) (k + 2) = (k + 1)/(k + 2) … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

Then,

1/1.2 + 1/2.3 + 1/3.4 + … + 1/k(k + 1) + k/(k + 1) (k + 2)

= 1/(k + 1)/(k + 2) + k/(k + 1)

= 1/(k + 1) [k(k + 2)+1]/(k + 2)

= 1/(k + 1) [k

^{2}+ 2k + 1]/(k + 2)=1/(k + 1) [(k + 1) (k + 1)]/(k + 2)

= (k + 1) / (k + 2)

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 5. 1 + 3 + 5 + … + (2n – 1) = n^{2} i.e., the sum of first n odd natural numbers is n^{2}.

**Solution:**

Let P (n) = 1 + 3 + 5 + … + (2n – 1) = n

^{2}Step 1:

Now, let us check P(n) for n=1.

P (1) = 1 = 1

^{2 }= 1So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1 + 3 + 5 + … + (2k – 1) = k

^{2}… (i)Step 3:

Now, we have to prove for P(k + 1) is true.

Then, 1 + 3 + 5 + … + (2k – 1) + 2(k + 1) – 1

= k

^{2}+ (2k + 1)= k

^{2}+ 2k + 1= (k + 1)

^{2}So, P (n) is true for n = k + 1

i.e, P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 6. 1/2.5 + 1/5.8 + 1/8.11 + … + 1/(3n – 1) (3n + 2) = n/(6n + 4)

**Solution:**

Let P (n) = 1/2.5 + 1/5.8 + 1/8.11 + … + 1/(3n – 1) (3n + 2) = n/(6n + 4)

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1/2.5 = 1/(6.1 + 4)

or, 1/10 = 1/10

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1/2.5 + 1/5.8 + 1/8.11 + … + 1/(3k – 1) (3k + 2) = k/(6k + 4) … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1/2.5 + 1/5.8 + 1/8.11 + … + 1/(3k – 1)(3k + 2) + 1/(3k + 3 – 1)(3k + 3 + 2)

= k/(6k + 4) + 1/(3k + 2)(3k + 5)

= [k(3k + 5) + 2] / [2(3k + 2)(3k + 5)]

= (k + 1) / (6(k + 1) + 4)

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 7. 1/1.4 + 1/4.7 + 1/7.10 + … + 1/(3n – 2)(3n + 1) = n/3n + 1

**Solution:**

Let P (n) = 1/1.4 + 1/4.7 + 1/7.10 + … + 1/(3n – 2)(3n + 1) = n/3n + 1

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1/1.4 = 1/4

Or, 1/4 = 1/4

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1/1.4 + 1/4.7 + 1/7.10 + … + 1/(3k – 2)(3k + 1) = k/3k + 1 … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

Then, [1/1.4 + 1/4.7 + 1/7.10 + … + 1/(3k – 2)(3k + 1)] + 1/(3k + 1)(3k + 4)

= k/(3k + 1) + 1/(3k + 1)(3k + 4)

= 1/(3k + 1) [k/1 + 1/(3k + 4)]

= 1/(3k + 1) [k(3k + 4) + 1]/(3k + 4)

= 1/(3k + 1) [3k

^{2}+ 4k + 1]/ (3k + 4)= 1/(3k + 1) [3k

^{2}+ 3k + k + 1]/(3k + 4)= [3k(k + 1) + (k + 1)] / [(3k + 4) (3k + 1)]

= [(3k + 1)(k + 1)] / [(3k + 4) (3k + 1)]

= (k + 1) / (3k + 4)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 8. 1/3.5 + 1/5.7 + 1/7.9 + … + 1/(2n + 1)(2n + 3) = n/3(2n + 3)

**Solution:**

Let P (n) = 1/3.5 + 1/5.7 + 1/7.9 + … + 1/(2n + 1)(2n + 3) = n/3(2n + 3)

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1/3.5 = 1/3(2.1 + 3)

or, 1/15 = 1/15

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P(k) = 1/3.5 + 1/5.7 + 1/7.9 + … + 1/(2k + 1)(2k + 3) = k/3(2k + 3) … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

Then, 1/3.5 + 1/5.7 + 1/7.9 + … + 1/(2k + 1)(2k + 3) + 1/[2(k + 1) + 1][2(k + 1) + 3]

1/3.5 + 1/5.7 + 1/7.9 + … + 1/(2k + 1)(2k + 3) + 1/(2k + 3)(2k + 5)

Now putting the value of (i), we get,

= k/3(2k + 3) + 1/(2k + 3)(2k + 5)

= [k(2k + 5) + 3] / [3(2k + 3)(2k + 5)]

= (k + 1) / [3(2(k + 1) + 3)]

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 9. 1/3.7 + 1/7.11 + 1/11.15 + … + 1/(4n – 1)(4n + 3) = n/3(4n + 3)

**Solution:**

Let P (n) = 1/3.7 + 1/7.11 + 1/11.15 + … + 1/(4n – 1)(4n + 3) = n/3(4n + 3)

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1/(3.7) = 1/((4.1 – 1)(4 + 3))

Or, 1/21 = 1/21

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1/3.7 + 1/7.11 + 1/11.15 + … + 1/(4k – 1)(4k + 3) = k/3(4k + 3) … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

Then, 1/3.7 + 1/7.11 + 1/11.15 + … + 1/(4k – 1)(4k + 3) + 1/(4k + 3)(4k + 7)

Now putting the value of (i), we get,

= k/(4k + 3) + 1/(4k + 3)(4k + 7)

= 1/(4k + 3) [k(4k + 7) + 3] / [3(4k + 7)]

= 1/(4k + 3) [4k

^{2}+ 7k + 3]/ [3(4k + 7)]= 1/(4k + 3) [4k

^{2}+ 3k + 4k + 3] / [3(4k + 7)]= 1/(4k + 3) [4k(k + 1) + 3(k + 1)]/ [3(4k + 7)]

= 1/(4k + 3) [(4k + 3)(k + 1)] / [3(4k + 7)]

= (k + 1) / [3(4k + 7)]

So, P (n) is true for n = k + 1

i.e, P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 10. 1.2 + 2.2^{2} + 3.2^{3} + … + n.2^{n} = (n – 1) 2^{n+1} + 2

**Solution:**

Let P (n) = 1.2 + 2.2

^{2}+ 3.2^{3}+ … + n.2^{n}= (n – 1) 2^{n+1 }+ 2Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1.2 = 0.2

^{0 }+ 2or, 2 = 2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) =1.2 + 2.2

^{2}+ 3.2^{3}+ … + k.2^{k}= (k – 1) 2^{k+1}+ 2 … (i)Step 3:

Now, we have to prove for P(k+1) is true.

Then, [1.2 + 2.2

^{2}+ 3.2^{3}+ … + k.2^{k}] + (k + 1)2k + 1Now, putting the value of (i), we get,

= [(k – 1)2

^{k+1}+ 2] + (k + 1)2^{k+1}= (k – 1)2

^{k+1}+ 2 + (k + 1)2^{k+1}= 2

^{k+1}(k – 1 + k + 1) + 2= 2

^{k+1}× 2k + 2= k.2

^{k+2}+ 2So, P (n) is true for n = k + 1

i.e, P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 11. 2 + 5 + 8 + 11 + … + (3n – 1) = 1/2 n (3n + 1)

**Solution:**

Let P (n) = 2 + 5 + 8 + 11 + … + (3n – 1) = 1/2 n (3n + 1)

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 2 = 1/2 × 1 × 4

or, 2 = 2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 2 + 5 + 8 + 11 + … + (3k – 1) = 1/2 k (3k + 1) … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

Then, 2 + 5 + 8 + 11 + … + (3k – 1) + (3k + 2)

Now, putting the value (i), we get,

= 1/2 × k (3k + 1) + (3k + 2) (using equation (i))

= [3k

^{2}+ k + 2 (3k + 2)] / 2= [3k

^{2}+ k + 6k + 2] / 2= [3k

^{2}+ 7k + 2] / 2= [3k

^{2}+ 4k + 3k + 2] / 2= [3k (k + 1) + 4(k + 1)] / 2

= [(k + 1) (3k + 4)] /2

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 12. 1.3 + 2.4 + 3.5 + … + n. (n + 2) = 1/6 n (n + 1) (2n + 7)

**Solution:**

Let P (n) = 1.3 + 2.4 + 3.5 + … + n. (n + 2) = 1/6 n (n + 1) (2n + 7)

Step 1:

Now, let us check P(n) for n=1.

P (1) = 1.3 = 1/6 × 1 × 2 × 9

Or, 3 = 3

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1.3 + 2.4 + 3.5 + … + k. (k + 2) = 1/6 k (k + 1) (2k + 7) … (i)

Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1.3 + 2.4 + 3.5 + … + k. (k + 2) + (k + 1) (k + 3)

Now, putting the value (i), we get,

= 1/6 k (k + 1) (2k + 7) + (k + 1) (k + 3) (using equation (i))

= (k + 1) [{k(2k + 7)/6} + {(k + 3)/1}]

= (k + 1) [(2k

^{2}+ 7k + 6k + 18)] / 6= (k + 1) [2k

^{2}+ 13k + 18] / 6= (k + 1) [2k

^{2}+ 9k + 4k + 18] / 6= (k + 1) [2k(k + 2) + 9(k + 2)] / 6

= (k + 1) [(2k + 9) (k + 2)] / 6

= 1/6 (k + 1) (k + 2) (2k + 9)

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 13. 1.3 + 3.5 + 5.7 + … + (2n – 1) (2n + 1) = n(4n^{2} + 6n – 1)/3

**Solution:**

Let P (n) = 1.3 + 3.5 + 5.7 + … + (2n – 1) (2n + 1) = n(4n

^{2}+ 6n – 1)/3Step 1:

Now, let us check P(n) for n = 1.

P (1) = : (2.1 – 1) (2.1 + 1) = 1(4.1

^{2}+ 6.1 – 1)/3or, 1 × 3 = 1(4 + 6 – 1)/3

or, 3 = 3

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1.3 + 3.5 + 5.7 + … + (2k – 1) (2k + 1) = k(4k

^{2}+ 6k – 1)/3 … (i)Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1.3 + 3.5 + 5.7 + … + (2k – 1) (2k + 1) + (2k + 1) (2k + 3)

Now, putting the value (i), we get,

= k(4k

^{2}+ 6k – 1)/3 + (2k + 1) (2k + 3) (using equation (i))= [k(4k

^{2}+ 6k-1) + 3 (4k^{2}+ 6k + 2k + 3)] / 3= [4k

^{3}+ 6k^{2}– k + 12k^{2}+ 18k + 6k + 9] /3= [4k

^{3}+ 18k^{2}+ 23k + 9] /3= [4k

^{3}+ 4k^{2}+ 14k^{2}+ 14k + 9k + 9] /3= [(k + 1) (4k

^{2}+ 8k +4 + 6k + 6 – 1)] / 3= [(k + 1) 4[(k + 1)

^{2}+ 6(k + 1) -1]] /3So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 14. 1.2 + 2.3 + 3.4 + … + n(n + 1) = [n (n + 1) (n + 2)] / 3

**Solution:**

Let P (n) = 1.2 + 2.3 + 3.4 + … + n(n + 1) = [n (n + 1) (n + 2)] / 3

Step 1:

Now, let us check P(n) for n = 1.

P (1) = 1(1 + 1) = [1(1 + 1) (1 + 2)] /3

or, 2 = 2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1.2 + 2.3 + 3.4 + … + k(k+1) = [k (k + 1) (k + 2)] / 3 … (i)

Step 3:

Now, we have to prove for P(k + 1) is true.

Then, 1.2 + 2.3 + 3.4 + … + k(k + 1) + (k + 1) (k + 2)

Now, putting the value (i), we get,

= [k (k + 1) (k + 2)] / 3 + (k + 1) (k + 2)

= (k + 2) (k + 1) [k/2 + 1]

= [(k + 1) (k + 2) (k + 3)] /3

So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 15. 1/2 + 1/4 + 1/8 + … + 1/2^{n} = 1 – 1/2^{n}

**Solution:**

Let P (n) = 1/2 + 1/4 + 1/8 + … + 1/2

^{n}= 1 – 1/2^{n}Step 1:

Now, let us check P(n) for n=1.

P (1) = 1/2

^{1}= 1 – 1/2^{1}or, 1/2 = 1/2

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = : 1/2 + 1/4 + 1/8 + … + 1/2

^{k}= 1 – 1/2^{k}… (i)Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1/2 + 1/4 + 1/8 + … + 1/2

^{k}+ 1/2^{k+1}Now, putting the value (i), we get,

= 1 – 1/2

^{k}+ 1/2^{k+1}(using eq(i))= 1 – ((2 – 1)/2

^{k+1})So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.

### Question 16. 1^{2} + 3^{2} + 5^{2} + … + (2n – 1)^{2} = 1/3 n (4n^{2} – 1)

**Solution:**

Let P (n) = 1

^{2}+ 3^{2}+ 5^{2}+ … + (2n – 1)^{2}= 1/3 n (4n^{2}– 1)Step 1:

Now, let us check P(n) for n=1.

P (1) = (2.1 – 1)

^{2}= 1/3 × 1 × (4 – 1)or, 1 = 1

So, P(1) is true.

Step 2:

Let us consider P (n) be the true for n = k,

P (k) = 1

^{2}+ 3^{2}+ 5^{2}+ … + (2k – 1)^{2}= 1/3 k (4k^{2}– 1) … (i)Step 3:

Now, we have to prove for P(k+1) is true.

Then, 1

^{2}+ 3^{2}+ 5^{2}+ … + (2k – 1)^{2}+ (2k + 1)^{2}Now, putting the value (i) ,we get,

Or, 1/3 k (4k

^{2}– 1) + (2k + 1)^{2}(using eq(i))= 1/3 k (2k + 1) (2k – 1) + (2k + 1)

^{2}= (2k + 1) [{k(2k – 1)/3} + (2k + 1)]

= (2k + 1) [2k

^{2}– k + 3(2k + 1)] / 3= (2k + 1) [2k

^{2}– k + 6k + 3] / 3= [(2k + 1) 2k

^{2}+ 5k + 3] /3= [(2k + 1) (2k(k + 1)) + 3 (k + 1)] /3

= [(2k + 1) (2k + 3) (k + 1)] /3

= (k + 1)/3 [4k

^{2}+ 6k + 2k + 3]= (k + 1)/3 [4k

^{2}+ 8k – 1]= (k + 1)/3 [4(k + 1)

^{2}– 1]So, P (n) is true for n = k + 1

i.e., P (n) is true for all n ∈ N

Hence, by principle of Mathematical Induction (PMI), P (n) is true for all n ∈ N.